Economic evaluation of a haemophilus influenzae type B meningitis prevention program in Manila, Philippines - Limcangco, Maria Rhona
Effective vaccines against Haemophilus influenzae type B (HiB) have shown impressive results in decreasing Hib meningitis in western countries. In the Philippines, Hib vaccine is not yet part of the Expanded Program on Immunization (EPI). The high cost of Hib vaccine makes it prudent to determine its costs and benefits before its incorporation in the EPI. OBJECTIVES: The objectives of this study were to determine the epidemiology of Hib meningitis in Manila, Philippines and to evaluate the costs and benefits of immunising against Hib meningitis. METHODOLOGY: Epidemiological design: A cohort of 41,592 children under 5 years of age in Central Manila was the study population. Confirmed cases between January 1994 and December 1996 were obtained from all hospitals in the region. Confirmation of cases was based on: (i) positive culture isolated from blood or cerebrospinal fluid (CSF) or (ii) Hib-antigen identified in CSF with a clinical diagnosis of Hib meningitis. The progress of children with Hib meningitis post-infection was evaluated from hospital records. ECONOMIC MODEL: The state of health of the cohort was modelled each month for a five-year period. A survey of medical records of children included in the study provided the data on the extent and cost of sequelae following infection. RESULTS: There were 118 episodes of Hib meningitis identified in the population in the time period. Sequelae occurred in 15% of the total cases and the case fatality rate was 11%. The annual incidence of Hib meningitis in Manila for children under 5 is 95 per 100,000. The model predicted that in the absence of a preventive intervention against Hib meningitis, there will be 980 new cases per year in the birth cohort in Manila. A 3-dose program that aims to vaccinate children at ages 2, 3 and 4 months given the base case assumptions (90% vaccine efficacy, 85% vaccination rate, 95 per 100,000 incidence) will reduce this number to 427 cases per year. The result of the cost-benefit analysis indicates that the cost generated by Hib meningitis from the perspective of the Society exceeded the costs associated with such a vaccination program. CONCLUSION: This work has shown that there are positive economic benefits for Manila and Philippine society if a vaccination program is introduced and it is hoped that results may provide important evidence to assist in the decision making process.
Available to the general public.
Thesis (Master of Pharmacy)--University of Sydney, March 1998.
Keywords: Haemophilus influenzae -- Philippines -- Manila -- Prevention -- Economic aspects; Haemophilus meningitis -- Philippines -- Manila -- Prevention -- Economic aspects; Public health -- Philippines -- Manila -- Evaluation -- Economic aspects